(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This article discusses some morphological, physiological characteristics, nutritional value of the peanut (Arachis hypogeae) plant. At the same time, information on resistance to abiotic factors, differences in morphological features, and peanut cultivation technologies is provided.